Family-based association tests: FBAT testing strategies for large-scale association studies - Lange, Christoph (Henry Stewart Talks, 2007)
Genome-wide association studies, Using the same data set for screening and testing, The conditional mean model, The FBAT-statistic, Genetic model under the alternative hypothesis, The concept of the conditional mean model, The screening technique for multiple markers, PBAT's screening techniques for multiple SNPs, The 3 steps of the screening technique, The Framingham heart study, Replication (recessive model) from other studies, Important observations from Herbert et al. (2006), Summary of the approach, Extensions, Software implementation
Archived at 2025/05/28